Perceived performance of health facility governing committees in overseeing healthcare services delivery in primary health care facilities in Tanzania. (21st September 2022) - Kesale, Anosisye M.; Jiyenze, Mwandu Kini; Katalambula, Leonard; Kinyaga, Ally Y.; Sirili, Nathanael; Ngocho, James S.; Ruhago, George; Kikula, Amani; Kapologwe, Ntuli A.; Kengia, James T.
Abstract: Health Facility Governing Committees (HFGCs) play a vital role in overseeing health services delivery in the primary health care system. However, despite their existence in Tanzania hiccups remain reported on the quality of health services delivered in primary health care facilities. The latter poses a question on the performance of HFGCs in overseeing the services delivery at the primary health facilities. This study sought to assess the perceived performance of the HFGCs and the associated factors in overseeing the healthcare services delivery at the primary health facilities in Tanzania. A cross‐sectional study was conducted in five regions of Tanzania: Mwanza, Dar Es Salaam, Kilimanjaro, Pwani, and Arusha. A self‐administered questionnaire containing structured questions was used to gather information from randomly selected 574 HFGC members. Data were analyzed descriptively and the binary logistic regression model was used to determine factors associated with the perceived performance. Half (50.52%) of the HFGCs members perceived themselves to have good performance. Furthermore, only 51.05% of all the participants had received any form of health management and governance training whereby about two‐thirds had received training for only 1 day. The main factors associated with the perceived low performance of the HFGCs members were age, level of education and duration served in the HFGC. A low level of education was associated with the poor perceived performance of the HFGC (AOR 0.36 [CI: 0.23–0.55]). Similarly with increasing age, the odds of good‐perceived performance lowered (AOR 0.26 [CI: 0.13, 0.55]). Serving as a HFGC member for less than 1 year was associated with poor perceived performance (AOR 0.40 [CI: 0.17, 0.95]). From these findings, it is recommended that the criteria for recruitment of HFGC members should be revisited. Furthermore, a qualitative study to explore contextual factors influencing the perforce of HFGCs is recommended. Highlights: Effective community participation through Health Facility Governing Committees (HFGCs) is critical in improving the delivery of primary health care. Half of the HFGCs members perceived themselves to have low performance. Age, education level and experience of the HFGCs members are associated with low performance among HFGCs members. There is a need for reviewing the educational qualification criteria of HFGCs members to strengthen their management and governance capacities.